Fabricating Modish Mobile Application for a Visionless Citizen to Act as a Visioned Citizen - Jananee V; Shalini P; Dhivya S (Institute of Advanced Engineering and Science, 2018)
Technology has its wide range of applications in every field potentially even on the Mobile technology. One of the technologies which accomplish the blind person in android mobile is Virtual Reality. In spite of virtual reality is engaged to effectuate the operations, the blind person attention is one of the most important statistics. Although mobile devices include operative features available for amaurotic users, the user interface of the greater part of the mobile apps is designed for sighted people. If they carry out any mistakes to use the apps it may lead to a wrong call. So, one may think of a technology that diminishes the anxiety of a blind person for using apps. The proposed system converts the text into audio for giving the directions to the blind person about the gestures inferred. For such conversion a technique called speech synthesizer is used. Assorted innovative tools are used in mobile phones. Blind people need to confide in normal person for creating and updating a contact. Our project incorporates the gestures from the blind people and confirms the gestures through voice. Gesture conversion is accomplished by using haptic technology. An amaurotic person can create a new contact and they can invoke the contact by using this voice confirmation. During calling if there is multiple contact list, caller setting are initialized and ask the preference from the blind people, progress the voice call.